2019
DOI: 10.3390/ijms20040943
|View full text |Cite
|
Sign up to set email alerts
|

Root Proteomics Reveals the Effects of Wood Vinegar on Wheat Growth and Subsequent Tolerance to Drought Stress

Abstract: Wood vinegar (WV) or pyroligneous acid (PA) is a reddish-brown liquid created during the dry distillation of biomass, a process called pyrolysis. WV contains important biologically active components, which can enhance plant growth and tolerance to drought stress. However, its mechanism of action remains unknown. Our results after presoaking wheat seeds with various concentrations of WV indicate that a 1:900 WV concentration can significantly enhance growth. To investigate the response of wheat roots to drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 82 publications
5
41
0
4
Order By: Relevance
“…This suggested the existence of isoforms and posttranslational modification. Similar results were also found in others [24,33]. Taken together, the 60 identities represented 49 unique proteins (Tables S2 and S4).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This suggested the existence of isoforms and posttranslational modification. Similar results were also found in others [24,33]. Taken together, the 60 identities represented 49 unique proteins (Tables S2 and S4).…”
Section: Resultssupporting
confidence: 86%
“…In particular, high temperature [16,17], low temperature [18,19], drought [20], and water-stress [21] can result in male sterility in crops, including Hordeum vulgare [22], Oryza sativa [23], Triticum aestivum [18]. Meanwhile, proteomics is a powerful approach to study the molecular processes of pollen development, and also a powerful complement to the whole genome sequencing [24]. Based on the proteins identified in this work, a detailed pathway was successfully constructed and protein-protein interactions were more clearly understood [25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, proteomics analyses of different plants under both salinity and drought stresses were conducted to find the osmotic response proteins [12,13,14,15,16,17]. Drought and salinity are two serious kinds of osmotic stresses that inhibit plant growth and crop yields.…”
mentioning
confidence: 99%
“…In another drought-tolerant wheat variety, 335 drought-responsive proteins were found to mainly take part in photosynthesis, carbon fixation, and glyoxylate and dicarboxylate metabolism [13]. In addition, a comparative analysis of filling-kernel proteomes from two maize inbred lines with different drought-tolerant ability identified 5175 drought-responsive proteins [14]. Proteomics study implied that wood vinegar treatment can enhance the drought tolerance of wheat root through promoting stress response, carbohydrate metabolism, protein metabolism, and secondary metabolism [15].…”
mentioning
confidence: 99%
“…Studies have shown that peroxidase abundance and activity of peroxidase increased significantly in tomato roots under Cd stress (Borges, 2018). Research with wheat were observer variation in peroxidases and other proteins involved in the scavenging mechanisms in response to drug stress in as well (Wang et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%